Common Bean Yield and Zinc Use Efficiency in Association with Diazotrophic Bacteria Co-Inoculations - Arshad Jalal; Fernando Shintate Galindo; Eduardo Henrique Marcandalli Boleta; Carlos Eduardo da Silva Oliveira; André Rodrigues dos Reis; Thiago Assis Rodrigues Nogueira; Mário João Moretti Neto; Emariane Satin Mortinho; Guilherme Carlos Fernandes; Marcelo Carvalho Minhoto Teixeira Filho (Agronomy, 2021)
Enrichment of staple food with zinc (Zn) along with solubilizing bacteria is a sustainable and practical approach to overcome Zn malnutrition in human beings by improving plant nutrition, nutrient use efficiency, and productivity. Common bean (Phaseolus vulgaris L.) is one of a staple food of global population and has a prospective role in agronomic Zn biofortification. In this context, we evaluated the effect of diazotrophic bacterial co-inoculations (No inoculation, Rhizobium tropici, R. tropici + Azospirillum brasilense, R. tropici + Bacillus subtilis, R. tropici + Pseudomonas fluorescens, R. tropici + A. brasilense + B. subtilis, and R. tropici + A. brasilense + P. fluorescens) in association with soil Zn application (without and with 8 kg Zn ha−1) on Zn nutrition, growth, yield, and Zn use efficiencies in common bean in the 2019 and 2020 crop seasons. Soil Zn application in combination with R. tropici + B. subtilis improved Zn accumulation in shoot and grains with greater shoot dry matter, grain yield, and estimated Zn intake. Zinc use efficiency, recovery, and utilization were also increased with co-inoculation of R. tropici + B. subtilis, whereas agro-physiological efficiency was increased with triple co-inoculation of R. tropici + A. brasilense + P. fluorescens. Therefore, co-inoculation of R. tropici + B. subtilis in association with Zn application is recommended for biofortification and higher Zn use efficiencies in common bean in the tropical savannah of Brazil.